2010
DOI: 10.1111/j.1365-2621.2010.02461.x
|View full text |Cite
|
Sign up to set email alerts
|

Effect of banana and soybean hull flours on vacuum-packaged chicken nuggets during refrigeration storage

Abstract: The green banana flour (GBF), soybean hull flour (SHF) and combination (50:50) of GBF and SHF were added at the level of 4% each to evaluate the storage characteristics of chicken nuggets. The pH values were declined (P < 0.05) over storage periods. Lipid oxidation products were higher (P < 0.05) in control samples; however, they were increased in all samples with the increase in storage time. GBF-added samples had lower (P < 0.05) free fatty acid contents when compared to other treated nuggets including contr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
17
1
3

Year Published

2011
2011
2019
2019

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 25 publications
(28 citation statements)
references
References 39 publications
(80 reference statements)
7
17
1
3
Order By: Relevance
“…Modi et al (2007) reported that freshly prepared dehydrated chicken kebab mix had FFA value of 0.99% which increased significantly (P < 0.05) to 1.74% during 6 months of storage. Similar increase in FFA content during storage has also been reported by Nayak and Tanwar (2004), Nagamallika et al (2006) in chicken patties, Das et al (2008) in goat meat patties and Kumar et al (2011) in chicken nuggets. In general, FFA content alone did not act as criteria for acceptability of products but it is a good quality indicator for oxidative changes in the meat products during storage.…”
Section: Ageing Stability Of Chevon Pattiessupporting
confidence: 85%
“…Modi et al (2007) reported that freshly prepared dehydrated chicken kebab mix had FFA value of 0.99% which increased significantly (P < 0.05) to 1.74% during 6 months of storage. Similar increase in FFA content during storage has also been reported by Nayak and Tanwar (2004), Nagamallika et al (2006) in chicken patties, Das et al (2008) in goat meat patties and Kumar et al (2011) in chicken nuggets. In general, FFA content alone did not act as criteria for acceptability of products but it is a good quality indicator for oxidative changes in the meat products during storage.…”
Section: Ageing Stability Of Chevon Pattiessupporting
confidence: 85%
“…Modi et al (2007) reported that freshly prepared dehydrated chicken kebab mix had FFA values of 0.99%, which gradually (P<0.05) increased to 1.74% during 6 months of storage. The FFA increased as storage days increases, and according to Kumar et al (2011) the FFA in green banana flour treated and vacuum packaged chicken meat nuggets was increased due to growth of certain species of bacteria during refrigeration storage. Lower FFA observed in the present study could be attributed to presence of lower level of fat in all the products.…”
Section: Resultsmentioning
confidence: 99%
“…According to the authors, the pH values of the products decreased with increasing amounts of apple pulp. Kumar et al (2010) reported controversial results when analysing the pH values of chicken nuggets produced with banana fl our and soybean skin (1 to 5%), where no signifi cant differences were found amongst the treatments.…”
Section: Ph Analysismentioning
confidence: 99%
“…The inclusion of dietary fi bres as ingredients in meat products has been considered of interest for the partial replacement of the meat, due to their inherent functional and nutritional effects (HUR et al, 2009;KUMAR et al, 2010).…”
Section: Introductionmentioning
confidence: 99%